BRAND LEGACY DAN EKSISTENSI ERA INDONESIA DALAM PERSAINGAN BROKER PROPERTI DIGITAL - Iwan Setiawan (Insani, 2025)
The real estate brokerage industry in Indonesia has become increasingly competitive due to the growing use of digital platforms, the emergence of independent property agents, and changes in consumer behavior in searching, comparing, and deciding on property purchases. In this context, ERA Indonesia, as a relevant case and as one of the long-established real estate brokerage brands, becomes an interesting phenomenon to examine. This study aims to explain the factors supporting the existence of ERA Indonesia as a legacy brand in the Indonesian property brokerage industry. This research employs a descriptive qualitative approach with a case study method through literature review, document analysis from the available sources, digital observation, and semi-structured interviews when data access is available. The discussion focuses on brand legacy, brand reputation, consumer trust, business networks, service quality, and organizational adaptation to market changes as an interrelated analytical framework. The study indicates that the existence of a legacy brand is shaped by a combination of market experience, brand recognition, reputation, service quality, consumer trust, and the ability to adapt to technological dynamics and customer needs. This article argues that brand legacy can serve as a competitive advantage in this research context when it is actively, adaptively, and relevantly managed in the modern real estate industry.